Optimizing digital out of home outdoor media by utilizing data to increase the effectiveness of marketing campaigns - Usman, Osly; Hardini, Inkreswari Retno; Kasofi, Adnan (Edelweiss Applied Science and Technology, 2025)
In the last 10 years, there have been many changes in various fields around the world, especially in advertising. Over the last decade, marketers have continued to evolve dynamically to keep up with the times and the needs of their consumers. One of the advertising media that is often used to this day is DOOH, or Digital Out of Home advertisement. External media (DOOH) is a traditional advertising medium that is still widely used today. However, with the development of digital technology, DOOH needs to be optimized to compete with other advertising media. This research aims to optimize DOOH by using data to improve the effectiveness of marketing campaigns. The data used includes demographics, location, and consumer behavior. The research contributes to the field of marketing by demonstrating how data can be used to optimize DOOH and enhance the effectiveness of marketing campaigns. The data generated will later serve as a reference for marketers intending to conduct marketing campaigns using DOOH media.